Organic-inorganic perovskite thin film, perovskite / crystalline silicon laminated solar cell and preparation method of organic-inorganic perovskite thin film and perovskite / crystalline silicon laminated solar cell
By using cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources to modify the inorganic frame and combine it with organic solutions in perovskite/crystalline silicon stacked solar cells, the problem of low quality of perovskite films is solved, and the photovoltaic performance and stability of solar cells are significantly improved.
Patent Information
- Application Number
- CN202411645254.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
In the preparation process of the perovskite film, existing perovskite/crystalline silicon stacked solar cells have problems such as difficulty in completely converting the inorganic framework into a perovskite structure, low film quality, high non-radiative recombination and short carrier life, resulting in insufficient photovoltaic performance and stability.
Cesium bromide, lead iodide and rubidium halide are used as inorganic evaporation sources to form a modified inorganic frame, and annealed after the organic solution is applied to the surface to prepare a high-quality organic-inorganic perovskite film.
Through the conversion of the modified inorganic framework to the perovskite structure, the quality of the perovskite film is improved, the photovoltaic performance and stability of the perovskite/crystalline silicon stacked solar cells are enhanced, and the ideal open circuit voltage, filling factor and photoelectric conversion efficiency are shown as higher ideal open circuit voltage, filling factor and photoelectric conversion efficiency.
Smart Images

Figure CN119546138A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photovoltaics, and in particular relates to an organic-inorganic perovskite film, a perovskite / crystalline silicon stacked solar cell and a preparation method thereof. Background Art
[0002] Perovskite / crystalline silicon tandem solar cells have become a research hotspot in the photovoltaic field in recent years due to their ultra-high efficiency and cost advantages that exceed the theoretical limit of single-junction cells. In order to reduce light reflection, crystalline silicon bottom cells have larger pyramids (usually 2-3μm). The traditional perovskite film deposition method is difficult to completely cover the tip of the pyramid due to its limited thickness (<1μm), increasing the risk of current shunting. Therefore, in order to achieve higher optical absorption, researchers usually prepare perovskite solar cells on silicon cells by first evaporating the inorganic framework and then spin-coating the organic salt.
[0003] However, the existing method of first evaporating the inorganic framework and then spin-coating the organic salt is prone to the following problems: 1. The inorganic framework is difficult to be completely converted into a perovskite structure; 2. The perovskite film is of low quality and has a high non-radiative recombination; 3. The carrier lifetime in the perovskite film is short and the transmission distance is limited.
[0004] Therefore, there is an urgent need to develop a method for preparing perovskite films that can improve the quality of perovskite films and thereby improve the photovoltaic performance and stability of perovskite / crystalline silicon tandem solar cells. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing an organic-inorganic perovskite film. In the process of preparing an inorganic framework, the present invention uses cesium bromide, lead iodide and rubidium halide as evaporation sources for evaporation, thereby achieving the modification of the inorganic framework, promoting the subsequent transformation of the inorganic framework into a perovskite structure, improving the quality of the organic-inorganic perovskite film, and further improving the photovoltaic performance and stability of the perovskite / crystalline silicon stacked solar cell.
[0006] Specifically, the present invention provides a method for preparing an organic-inorganic perovskite film, the method comprising the following steps:
[0007] (1) evaporating cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources to obtain an inorganic framework;
[0008] (2) An organic solution is coated on the surface of the inorganic framework, followed by annealing to obtain an organic-inorganic perovskite film.
[0009] In one or more embodiments, in step (1), the rubidium halide is selected from one or more of rubidium fluoride, rubidium chloride, rubidium bromide and rubidium iodide.
[0010] In one or more embodiments, in step (1), the temperature of the evaporation chamber is 25-30°C.
[0011] In one or more embodiments, in step (1), the vacuum degree of evaporation is 7×10-4-7×10-5Pa.
[0012] In one or more embodiments, in step (2), the solute in the organic solution is selected from one or more of formamidine hydroiodide, formamidine hydrobromide, methylamine thiocyanate, methylammonium chloride, methylamine hydroiodide and methylamine hydrobromide.
[0013] In one or more embodiments, in step (2), the solvent in the organic solution is selected from one or more of ethanol, isopropanol, n-butanol and n-pentanol.
[0014] In one or more embodiments, in step (2), the coating method is knife coating or slot coating.
[0015] In one or more embodiments, in step (2), the coating speed is 5-40 mm / s.
[0016] In one or more embodiments, in step (2), the coating temperature is 10-40°C.
[0017] In one or more embodiments, in step (2), the annealing temperature is 100-160°C.
[0018] In one or more embodiments, in step (2), the annealing time is 5-60 min.
[0019] In one or more embodiments, in step (2), the annealing humidity is 30%-45%.
[0020] The invention provides an organic-inorganic perovskite film prepared by the method described in the invention.
[0021] In one or more embodiments, the thickness of the organic-inorganic perovskite thin film is 600-1000 mm.
[0022] In one or more embodiments, the material of the organic-inorganic perovskite film is a material having a chemical formula of ABX 3 A perovskite structure material, wherein A is selected from one or more of formamidinium ion, methylamine ion, cesium ion and rubidium ion, B is lead ion, and X is selected from one or more of fluoride ion, chloride ion, bromide ion, iodide ion and thiocyanate ion.
[0023] The present invention provides a perovskite / crystalline silicon stacked solar cell comprising the organic-inorganic perovskite thin film of the present invention.
[0024] In one or more embodiments, the perovskite / crystalline silicon tandem solar cell includes a heterojunction silicon bottom cell, a hole transport layer, an organic-inorganic perovskite film, an electron transport layer, a transparent electrode layer, an anti-reflection layer and a metal grid line in sequence from the thickness direction.
[0025] The present invention provides a method for preparing the perovskite / crystalline silicon tandem solar cell of the present invention, the method comprising the following steps:
[0026] (1) Depositing a hole transport layer on the surface of a heterojunction silicon bottom cell;
[0027] (2) depositing an organic-inorganic perovskite film on the surface of the hole transport layer;
[0028] (3) depositing an electron transport layer on the surface of the organic-inorganic perovskite film;
[0029] (4) depositing a transparent electrode layer on the surface of the electron transport layer;
[0030] (5) depositing an anti-reflection layer on the surface of the transparent electrode layer;
[0031] (6) Depositing metal grid lines on the surface of the anti-reflection layer to obtain a perovskite / crystalline silicon stacked solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the structure of perovskite solar cells prepared according to some embodiments of the present invention, wherein 100 is a metal grid line, 200 is an anti-reflection layer, 300 is a transparent electrode layer, 400 and 500 constitute an electron transport layer, 600 is an organic-inorganic perovskite film, 700 and 800 constitute a hole transport layer, and 900 is a heterojunction silicon bottom cell. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0036] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0037] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0038] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0039] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0040] The present invention provides a method for preparing an organic-inorganic perovskite film, the method comprising the following steps:
[0041] (1) evaporating cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources to obtain an inorganic framework;
[0042] (2) An organic solution is coated on the surface of the inorganic framework, followed by annealing to obtain an organic-inorganic perovskite film.
[0043] In the present invention, the perovskite film prepared by using cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources has fewer non-radiative recombination defects and a higher ideal open circuit voltage. Furthermore, the photovoltaic device containing the perovskite film prepared by using cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources has a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency. Cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources have a synergistic effect, which has a synergistic effect on improving the performance of photovoltaic devices.
[0044] In the inorganic framework of step (1), the volume ratio of cesium bromide to rubidium halide can be (1-10): 1, for example, 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1. In the present invention, controlling the volume ratio of cesium bromide to rubidium halide within the above range is beneficial to improving the open circuit voltage, fill factor and photoelectric conversion efficiency of the device.
[0045] In the inorganic framework of step (1), the volume ratio of lead iodide to rubidium halide can be (10-100): 1, for example, 10: 1, 20: 1, 30: 1, 40: 1, 50: 1, 60: 1, 70: 1, 80: 1, 90: 1, 100: 1. In the present invention, the volume ratio of lead iodide to rubidium halide is controlled within the above range, which is beneficial to improving the open circuit voltage, fill factor and photoelectric conversion efficiency of the device.
[0046] In step (1), the rubidium halide may be one or more selected from rubidium fluoride, rubidium chloride, rubidium bromide and rubidium iodide. The perovskite film prepared using the above rubidium halide as an inorganic evaporation source component has fewer non-radiative recombination defects and a higher ideal open circuit voltage. Furthermore, the device of the perovskite film prepared using the inorganic evaporation source component of the rubidium halide of the present invention has a higher open circuit voltage, a higher fill factor and a higher photoelectric conversion efficiency.
[0047] In step (1), the temperature of the evaporation chamber may be 25-30°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C. In step (1), the vacuum degree of evaporation may be 7×10 -4 -7×10 -5 Pa, for example 7×10 -5 , 8×10 -5 ,9×10 -5 , 1×10 -4 , 2×10 -4 , 3×10 -4 , 4×10 -4 , 5×10 -4 , 6×10 -4 ,7×10 -4 .
[0048] In step (2), the solute in the organic solution may be one or more selected from formamidine hydroiodide (FAI), formamidine hydrobromide (FABr), methylamine thiocyanate (MASCN), methylammonium chloride (MACl), methylamine hydroiodide and methylamine hydrobromide.
[0049] In step (2), the solvent in the organic solution may be one or more selected from ethanol, isopropanol, n-butanol and n-pentanol.
[0050] In step (2), the total concentration of the solute in the organic solution can be 0.8-0.96 mol / L, for example, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L.
[0051] In step (2), the coating method can be blade coating or slit coating. In step (2), the coating speed can be 5-40 mm / s, such as 5 mm / s, 10 mm / s, 15 mm / s, 20 mm / s, 25 mm / s, 30 mm / s, 35 mm / s, 40 mm / s. In step (2), the coating temperature can be 10-40°C, such as 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C.
[0052] In step (2), the annealing temperature can be 100-160° C., such as 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C. In step (2), the annealing time can be 5-60 min, such as 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min. In step (2), the annealing humidity can be 30%-45%.
[0053] In the present invention, the thickness of the organic-inorganic perovskite film may be 600-1000 mm, for example, 600 mm, 700 mm, 800 mm, 900 mm, 1000 mm.
[0054] In the present invention, the material of the organic-inorganic perovskite film is a material having a chemical formula of ABX 3 A perovskite structure material, wherein A can be one or more selected from formamidinium ion, methylamine ion, cesium ion and rubidium ion, B can be lead ion, and X can be one or more selected from fluoride ion, chloride ion, bromide ion, iodide ion and thiocyanate ion.
[0055] The present invention provides a perovskite / crystalline silicon tandem solar cell comprising an organic-inorganic perovskite film of the present invention. In the present invention, the perovskite / crystalline silicon tandem solar cell may include a heterojunction silicon bottom cell, a hole transport layer, an organic-inorganic perovskite film, an electron transport layer, a transparent electrode layer, an anti-reflection layer and a metal grid line in sequence from the thickness direction. The heterojunction silicon bottom cell of the present invention may also include an interconnection layer.
[0056] In the present invention, the hole transport layer can be selected from one or more of nickel oxide, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz) and 2-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz). In the present invention, the thickness of the hole transport layer can be 10-20nm, for example, 10mm, 12mm, 14mm, 16mm, 18mm, 20mm.
[0057] In the present invention, the electron transport layer may be C60 and / or SnO 2 In the present invention, the thickness of the electron transport layer may be 20-40 nm, for example, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm. In the present invention, the transparent electrode layer may be indium zinc oxide (IZO) and / or indium tin oxide. In the present invention, the thickness of the transparent electrode layer may be 40-70 nm, for example, 40 mm, 50 mm, 60 mm, 70 mm.
[0058] In the present invention, the antireflection layer may be magnesium fluoride and / or lithium fluoride. In the present invention, the thickness of the antireflection layer may be 50-200 nm, for example, 50 mm, 100 mm, 150 mm, 200 mm.
[0059] In the present invention, the metal grid line can be silver. In the present invention, the thickness of the metal grid line can be 200-1000nm, for example, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm, 900mm, 1000mm.
[0060] The present invention provides a method for preparing a perovskite / crystalline silicon tandem solar cell of the present invention, the method comprising the following steps:
[0061] (1) Depositing a hole transport layer on the surface of a heterojunction silicon bottom cell;
[0062] (2) depositing an organic-inorganic perovskite film on the surface of the hole transport layer;
[0063] (3) depositing an electron transport layer on the surface of the organic-inorganic perovskite film;
[0064] (4) depositing a transparent electrode layer on the surface of the electron transport layer;
[0065] (5) depositing an anti-reflection layer on the surface of the transparent electrode layer;
[0066] (6) Depositing metal grid lines on the surface of the anti-reflection layer to obtain a perovskite / crystalline silicon stacked solar cell.
[0067] In the present invention, the hole transport layer may be deposited by sputtering, spin coating, coating or evaporation. In the present invention, the electron transport layer may be deposited by evaporation or atomic layer deposition. In the present invention, the transparent electrode layer may be deposited by sputtering. In the present invention, the anti-reflection layer may be deposited by evaporation. In the present invention, the metal grid line may be deposited by evaporation or screen printing.
[0068] Compared with the prior art, the present invention has the following beneficial effects: the perovskite film prepared by the present invention has fewer non-radiative recombination defects and a higher ideal open circuit voltage; at the same time, the photovoltaic device prepared by the present invention has a higher open circuit voltage, fill factor and photoelectric conversion efficiency.
[0069] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0070] Example 1
[0071] First, the inorganic framework was prepared on a glass substrate using a co-evaporation method, where the evaporation source was PbI 2 , CsBr and RbCl, the temperature of the evaporation chamber is 30 °C, and the vacuum degree is -7×10 -5 Pa, the thickness of the inorganic framework is 405nm, PbI 2 , CsBr and RbCl volume ratio is 40:4:1; then use a scraper to coat the surface of the inorganic framework with an organic solution, wherein the solutes of the organic solution are FAI, FABr, MASCN and MACl, the mass ratios of FAI, FABr, MASCN and MACl are 481.9:350.2:67.4:50.5, the solvent of the organic solution is n-butanol, the total concentration of the solute in the organic solution is 0.8 mol / L, the solution volume is 60 μL, the coating speed is 20 mm / s, the scraper height is 300 μm, the air knife pressure is 0.2 MPa, and the coating temperature is 20°C; after the organic solution is coated, it is transferred to an annealing box for annealing treatment, wherein the annealing temperature is 120°C, the annealing time is 30 min, the annealing humidity is 30% to 40%, and the perovskite structure material is Rb 0.025 Cs 0.10 FA 0.875 PbI 2.4 Br 0.6 , organic-inorganic perovskite film with a thickness of 600nm.
[0072] Example 2
[0073] The other conditions of this example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbBr.
[0074] Example 3
[0075] The other conditions of this example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbI.
[0076] Example 4
[0077] The other conditions of this example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbF.
[0078] Comparative Example 1
[0079] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 and CsBr, the thickness of the prepared inorganic framework is 405nm, PbI 2 The volume ratio of CsBr is 10:1.
[0080] Comparative Example 2
[0081] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and NaCl.
[0082] Comparative Example 3
[0083] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and KCl.
[0084] Comparative Example 4
[0085] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and CsCl.
[0086] Comparative Example 5
[0087] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbBr 2 , CsBr and RbCl.
[0088] Comparative Example 6
[0089] The other conditions of this comparative example are the same as those of Example 1, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsI and RbCl.
[0090] Example 5
[0091] Preparation of this example Figure 1 The specific preparation steps of the crystalline silicon / perovskite stacked perovskite solar cell shown are as follows:
[0092] (1) preparing a nickel oxide layer on the surface of a heterojunction silicon bottom cell by a sputtering method to obtain a nickel oxide layer with a thickness of 15 nm; then spin coating 2PACz on the surface of the nickel oxide layer to obtain a 2PACz layer with a thickness of 2 nm, wherein the nickel oxide layer and the 2PACz layer together constitute a hole transport layer;
[0093] (2) First, an inorganic framework is prepared on the hole transport layer by co-evaporation, where the evaporation source is PbI 2 , CsBr and RbCl, the temperature of the evaporation chamber is 30 °C, and the vacuum degree is -7×10 -5 Pa, the thickness of the inorganic framework is 540nm, PbI 2 , CsBr and RbCl volume ratio is 40:4:1; then use a scraper to coat the surface of the inorganic framework with an organic solution, wherein the solutes of the organic solution are FAI, FABr, MASCN and MACl, the mass ratios of FAI, FABr, MASCN and MACl are 481.9:350.2:67.4:50.5, the solvent of the organic solution is n-butanol, the total concentration of the solute in the organic solution is 0.96 mol / L, the solution volume is 60 μL, the coating speed is 20 mm / s, the scraper height is 300 μm, the air knife pressure is 0.2 MPa, and the coating temperature is 20°C; after the organic solution is coated, it is transferred to an annealing box for annealing treatment, wherein the annealing temperature is 120°C, the annealing time is 30 min, the annealing humidity is 30% to 40%, and the perovskite structure material is Rb 0.025 Cs 0.10 FA 0.875 PbI 2.4 Br 0.6 , organic-inorganic perovskite film with a thickness of 800nm;
[0094] (3) A 16 nm thick C60 layer was prepared on the surface of the organic-inorganic perovskite film by evaporation, and a 11 nm thick SnO layer was prepared on the surface of the C60 layer by atomic layer deposition (ALD). 2 layer, C60 layer and SnO 2 The layers together constitute the electron transport layer;
[0095] (4) preparing an IZO layer on the surface of the electron transport layer by sputtering to obtain a transparent electrode layer with a thickness of 50 nm;
[0096] (5) preparing a magnesium fluoride layer on the surface of the transparent electrode layer by an evaporation method to obtain an anti-reflection layer with a thickness of 100 nm;
[0097] (6) Silver grid lines are prepared on the surface of the transparent electrode layer by an evaporation method to obtain metal grid lines with a thickness of 300 nm.
[0098] Example 6
[0099] The other conditions of this example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbBr.
[0100] Example 7
[0101] The other conditions of this example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbI.
[0102] Example 8
[0103] The other conditions of this example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and RbF.
[0104] Comparative Example 7
[0105] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 and CsBr, with a volume ratio of 10:1.
[0106] Comparative Example 8
[0107] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and NaCl.
[0108] Comparative Example 9
[0109] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and KCl.
[0110] Comparative Example 10
[0111] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsBr and CsCl.
[0112] Comparative Example 11
[0113] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbBr 2 , CsBr and RbCl.
[0114] Comparative Example 12
[0115] The other conditions of this comparative example are the same as those of Example 5, except that the evaporation source is different. The evaporation source of this comparative example is PbI 2 , CsI and RbCl.
[0116] Test Example 1
[0117] Performance test of organic-inorganic perovskite film: In an environment of 25°C, using an external quantum efficiency test equipment, the wavelength detection range is set to 650nm-850nm, and the external quantum efficiency (EQE) of the organic-inorganic perovskite film prepared in Examples 1-4 and Comparative Examples 1-6 under excitation light is tested, and the corresponding quasi-Fermi level splitting (mV) is calculated, wherein the wavelength of the incident light is 405nm and the incident light power is 100mW / cm 2 , the area of the luminous region is 0.05cm 2 The test results of the external quantum efficiency and the corresponding quasi-Fermi level splitting of the organic-inorganic perovskite films prepared in Examples 1-4 and Comparative Examples 1-6 are shown in Table 1.
[0118] Table 1: External quantum efficiency and corresponding quasi-Fermi level splitting of perovskite films prepared in Examples 1-4 and Comparative Examples 1-6
[0119] EQE(%) QFLS(mV) Example 1 0.97 1279.53 Example 2 0.81 1274.84 Example 3 0.79 1273.98 Example 4 0.65 1269.12 Comparative Example 1 0.30 1249.34 Comparative Example 2 0.25 1244.17 Comparative Example 3 0.24 1243.58 Comparative Example 4 0.17 1234.79 Comparative Example 5 0.12 1224.19 Comparative Example 6 0.10 1220.02
[0120] The corresponding quasi-Fermi level splitting data can be calculated through the external quantum efficiency, and the open circuit voltage is directly related to the quasi-Fermi level splitting. The quasi-Fermi level splitting reflects the filling level of electrons and holes in the energy band. The larger the splitting, the greater the difference in the concentration of electrons and holes, thereby generating a higher voltage. The larger the quasi-Fermi level splitting, the higher the open circuit voltage. Therefore, it can be seen from Table 1 that the perovskite film prepared by using cesium bromide, lead iodide and rubidium halide as inorganic framework evaporation sources in the embodiment of the present invention has an excellent and large quasi-Fermi level splitting, and the corresponding open circuit voltage is high.
[0121] Test Example 2
[0122] Photovoltaic performance test of perovskite / crystalline silicon tandem solar cells: At 25°C and AM 1.5G standard solar spectrum, a solar simulator was used to set the voltage range to 1.9V-0.1V, and the current output of the perovskite / crystalline silicon tandem solar cells prepared in Examples 5-8 and Comparative Examples 7-12 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 1.1664cm 2 , the incident light power (Pin) is 100mW / cm 2The photoelectric performance (open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency) of the perovskite / crystalline silicon tandem solar cells prepared in Examples 5-8 and Comparative Examples 7-12 were obtained according to the characteristic curves.
[0123] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.
[0124] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.
[0125] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc×Isc), where the maximum power point is the point where the battery output power reaches its maximum value.
[0126] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)×100%.
[0127] The test results of the photoelectric performance of the perovskite / crystalline silicon tandem solar cells prepared in Examples 5-8 and Comparative Examples 7-12 are shown in Table 2.
[0128] Table 2: Photovoltaic performance of perovskite / crystalline silicon tandem solar cells prepared in Examples 5-8 and Comparative Examples 7-12
[0129] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) Example 5 1.87 20.44 79.36 30.37 Example 6 1.87 20.42 79.12 30.21 Example 7 1.86 20.45 79.08 30.03 Example 8 1.87 20.42 78.77 30.06 Comparative Example 7 1.86 20.34 77.60 29.30 Comparative Example 8 1.84 19.92 77.35 28.35 Comparative Example 9 1.84 19.99 77.10 28.28 Comparative Example 10 1.83 19.96 77.78 28.47 Comparative Example 11 1.85 20.32 73.53 27.66 Comparative Example 12 1.84 20.53 71.39 26.97
[0130] As can be seen from Table 2, compared with the perovskite / crystalline silicon tandem solar cell in the comparative example containing a perovskite film prepared by an inorganic evaporation source other than the present invention, the perovskite / crystalline silicon tandem solar cell in the embodiment containing a perovskite film prepared by cesium bromide, lead iodide and rubidium halide inorganic evaporation sources has high open circuit voltage, fill factor and photoelectric conversion efficiency. Therefore, it can be explained that the inorganic evaporation source combination of the present invention can synergistically improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite / crystalline silicon tandem solar cell.
Claims
1. A method for preparing an organic-inorganic perovskite film, characterized in that: The method comprises the following steps: (1) evaporating cesium bromide, lead iodide and rubidium halide as inorganic evaporation sources to obtain an inorganic framework; (2) An organic solution is coated on the surface of the inorganic framework, followed by annealing to obtain an organic-inorganic perovskite film.
2. The method according to claim 1, characterized in that The method has one or more of the following features: In step (1), the rubidium halide is selected from one or more of rubidium fluoride, rubidium chloride, rubidium bromide and rubidium iodide; In step (1), the temperature of the evaporation chamber is 25-30°C; In step (1), the vacuum degree of evaporation is 7×10 -4 -7×10 -5 Pa.
3. The method according to claim 1, characterized in that In step (2), the solute in the organic solution is selected from one or more of formamidine hydroiodide, formamidine hydrobromide, methylamine thiocyanate, methylammonium chloride, methylamine hydroiodide and methylamine hydrobromide; and / or In step (2), the solvent in the organic solution is selected from one or more of ethanol, isopropanol, n-butanol and n-pentanol.
4. The method according to claim 1, characterized in that The method has one or more of the following features: In step (2), the coating method is blade coating or slit coating; In step (2), the coating speed is 5-40 mm / s; In step (2), the coating temperature is 10-40°C; In step (2), the annealing temperature is 100-160°C; In step (2), the annealing time is 5-60 min; In step (2), the annealing humidity is 30%-45%.
5. An organic-inorganic perovskite film, characterized in that: The organic-inorganic perovskite film is prepared by the method according to any one of claims 1 to 4.
6. The organic-inorganic perovskite thin film according to claim 5, characterized in that The thickness of the organic-inorganic perovskite film is 600-1000 mm.
7. The organic-inorganic perovskite thin film according to claim 5, characterized in that: The material of the organic-inorganic perovskite film is a perovskite structure material with a chemical formula of ABX3, wherein A is selected from one or more of formamidinium ions, methylamine ions, cesium ions and rubidium ions, B is a lead ion, and X is selected from one or more of fluoride ions, chloride ions, bromide ions, iodide ions and thiocyanate ions.
8. A perovskite / crystalline silicon tandem solar cell, characterized in that: The perovskite / crystalline silicon tandem solar cell comprises the organic-inorganic perovskite thin film according to any one of claims 5-7.
9. The perovskite / crystalline silicon tandem solar cell according to claim 8, characterized in that: The perovskite / crystalline silicon stacked solar cell comprises, in order from the thickness direction, a heterojunction silicon bottom cell, a hole transport layer, an organic-inorganic perovskite film, an electron transport layer, a transparent electrode layer, an anti-reflection layer and a metal grid line.
10. A method for preparing the perovskite / crystalline silicon tandem solar cell according to claim 8 or 9, characterized in that: The method comprises the following steps: (1) Depositing a hole transport layer on the surface of a heterojunction silicon bottom cell; (2) depositing an organic-inorganic perovskite film on the surface of the hole transport layer; (3) depositing an electron transport layer on the surface of the organic-inorganic perovskite film; (4) depositing a transparent electrode layer on the surface of the electron transport layer; (5) depositing an anti-reflection layer on the surface of the transparent electrode layer; (6) Depositing metal grid lines on the surface of the anti-reflection layer to obtain a perovskite / crystalline silicon stacked solar cell.